1997
DOI: 10.1016/s0006-3495(97)78159-1
|View full text |Cite
|
Sign up to set email alerts
|

Generation of action potentials in a mathematical model of corticotrophs

Abstract: Corticotropin-releasing hormone (CRH) is an important regulator of adrenocorticotropin (ACTH) secretion from pituitary corticotroph cells. The intracellular signaling system that underlies this process involves modulation of voltage-sensitive Ca2+ channel activity, which leads to the generation of Ca2+ action potentials and influx of Ca2+. However, the mechanisms by which Ca2+ channel activity is modulated in corticotrophs are not currently known. We investigated this process in a Hodgkin-Huxley-type mathemati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 42 publications
1
42
0
Order By: Relevance
“…There is indirect evidence suggesting that the agonist, by way of complex intracellular mechanisms, modulates the voltage sensitivity of the L-type Ca> channels embedded in the plasma membrane. We have previously constructed a Hodgkin}Huxley-type model of this process, which indicated that an increase in the L-type Ca> current is su$cient to generate repetitive action potentials (LeBeau et al (1997). Biophys.…”
mentioning
confidence: 99%
“…There is indirect evidence suggesting that the agonist, by way of complex intracellular mechanisms, modulates the voltage sensitivity of the L-type Ca> channels embedded in the plasma membrane. We have previously constructed a Hodgkin}Huxley-type model of this process, which indicated that an increase in the L-type Ca> current is su$cient to generate repetitive action potentials (LeBeau et al (1997). Biophys.…”
mentioning
confidence: 99%
“…It receives a negative feedback suppression of cortisol from the adrenal glands (Fuchsl et al, 2013). A patch-clamp experiment for membrane potential in single rat corticotrophs showed that CRH triggered a sustained [Ca 2+ ]i elevation and membrane depolarization for corticotrophs (Lee and Tse, 1997), and ACTH secretion was related to an increase in the L-type Ca 2+ current (LeBeau et al, 1997). Such an ACTH-releasing process is somehow like that of pancreatic β-cells, which release insulin through the L-type Ca 2+ channel triggered by the KATP channel (Aguilar-Bryan et al, 1995;Philipson and Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The remaining leak current (I Leak ) represents all other ionic current contributions not specifically described. The construction of these ionic currents from electrophysiological measurements in corticotrophs has previously been described in LeBeau et al (1997) (Alberts et al, 1983, p. 335). A schematic diagram of the ionic transport processes is shown in Fig.…”
Section: The Modelmentioning
confidence: 99%
“…A Hodgkin-Huxley-type mathematical model has been constructed which includes the major plasma membrane ionic currents identified in pituitary corticotrophs and the associated intracellular Ca 2+ dynamics (LeBeau et al, 1997;Shorten et al, 1999a). In certain parameter regimes the model exhibits a novel form of bursting behaviour.…”
Section: Introductionmentioning
confidence: 99%